Sonication-assisted nonpolar-antisolvent approach to produce cellulose suspensions, disaggregated by a nonpolar-antisolvent with orthogonal Kamlet-Taft acidity/basicity: Roles of net-basicity and cosolvency - Sergio E. Domínguez; Alexander S. Novikov; Dmitry A. Kornilov; Antti Vuolle; Mia Meriläinen; Hiram Isaac Beltrán (Ultrasonics Sonochemistry)
This work reports a simple sonication-assisted approach to produce diluted (0.5 mg/mL) suspensions of cellulose in the non-functionalizing nonpolar-antisolvent tetrahydrofuran (THF), which has a purely basic character (null Kamlet-Taft acidity parameter, α = 0), by using it as medium to sonicate microcrystalline cellulose (MCC) at 40 kHz/70 Watts. The suspensions are obtained because of the high reactivity of the amorphous regions within MCC and its capability to behave as a (Turbak) acid, together with the low viscosity and surface tension of THF, and most importantly because of the positive 0.55 net-basicity of THF, comparable to that of ionic liquids (ILs) or deep eutectic solvents (DESs) used to dissolve cellulose in polar conditions. This was demonstrated by chloroform (CHCl3), which cannot generate suspensions despite having similar values of viscosity, surface tension and molar volume than THF, however having a null basicity parameter, β = 0. (Complementary computational qualitative analyses using model molecules & conditions also show thermodynamic favorability of THF over CHCl3). FTIR suggest a decrease of around 5 % in the crystallinity of cellulose after sonication in THF, while DLS show that adding CHCl3 to the suspension in THF promotes disaggregation despite the THF-CHCl3 has a smaller net-basicity than THF, thus demonstrating cosolvency (instead of cononsolvency). (Complementary Langmuir trough experiments at the surface of water also demonstrate disaggregation because of CHCl3 instead of moisture).Despite the THF-CHCl3 pair has been used previously to analyze the supramolecular properties of different polymers, this work uses it to analyze disaggregation in two antisolvents. This approach could constitute a platform to perform studies of dissolution/regeneration under null polarity, using proper probes (e.g. ILs or DESs), substrates and matrices.